PENGARUH FOMO DAN FINANCIAL INFLUENCER DI MEDIA SOSIAL TERHADAP KEPUTUSAN INVESTASI CRYPTOCURRENCY GENERASI Z DENGAN LITERASI KRIPTO SEBAGAI VARIABEL MODERASI - Anggita Eka Syahrani Putri; Arie Setyo Dwi Purnomo (STKIP Pesisir Selatan, 2025)
This study is motivated by the growing interest of Generation Z in cryptocurrency investment, which is influenced by emotional and social factors in the digital era. The purpose of this research is to examine the effect of Fear of Missing Out (FoMO) and financial influencers on cryptocurrency investment decisions, as well as to analyze the moderating role of crypto literacy. This research employs a quantitative associative approach. The population consists of 15,483 students from the University of Trunojoyo Madura (cohorts 2022–2025), with a sample of 100 respondents selected using a purposive sampling technique. Data were collected using a Likert-scale questionnaire and analyzed using path analysis with SmartPLS 4.1.1.5. The results show that FoMO and financial influencers have a positive and significant effect on cryptocurrency investment decisions, while crypto literacy has a negative and significant effect. Moreover, crypto literacy negatively moderates the relationship between FoMO and financial influencers on investment decisions. This indicates that the higher an individual's level of crypto literacy, the weaker the emotional and social influence on their investment decision-making.